The impact of SARS‐CoV‐2 immunization on COVID‐19 disease course in people with myasthenia gravis. Issue 5 (3rd March 2023) - Bakirtzis, Christos; Boziki, Marina‐Kleopatra; Karakasi, Maria‐Valeria; Moysiadis, Theodoros; Grigoriadis, Nikolaos
Abstract: Introduction/Aims: There is limited knowledge regarding the impact of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) vaccines οn coronavirus disease 2019 (COVID‐19) disease course in people with myasthenia gravis. In this study, we aimed to investigate whether SARS‐CoV‐2 vaccination influences hospitalization and mortality due to COVID‐19 in this population. Methods: This is a retrospective analysis of administrative data extracted from the Greek nationwide database that holds the COVID‐19 disease and vaccination registry, as well as all medical prescription records. The study period extended from the onset of the pandemic (February 2020) until the 10th of January 2022. Results: We identified 278 people with myasthenia gravis (mean age 58.1 ± 17.2, 47.5% males) who tested positive for SARS‐CoV‐2. Of those, 139 (50%) were not vaccinated at the time of infection. Multivariable binary logistic regression analysis showed that the probability of hospitalization increased with age (odds ratio [OR]: 1.058; 95% confidence interval [CI], 1.036–1.080; p < .001) and immunosuppressive treatment (OR: 2.872; 95% CI 1.412–5.839; p = .004), and decreased with vaccination (OR: 0.244; 95% CI 0.132–0.453; p < .001). The probability of a fatal outcome increased with age (OR: 1.085; 95% CI 1.043–1.129; p < .001) and decreased with vaccination (OR: 0.315; 95% CI 0.125–0.791; p = .014). Discussion: SARS‐CoV‐2 vaccination significantly reduces hospitalization and mortality due to COVID‐19 in people with myasthenia gravis. This study regarding the efficacy of these vaccines, together with previous studies regarding their safety, provide evidence to support their use in people with myasthenia gravis.